Peranan Front Pembela Islam (FPI) Dalam Pemilihan Kepala Daerah dan Wakil Kepala Daerah Provinsi Daerah Khusus Ibu Kota Jakarta Tahun 2017 - Devi Harahap; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2019)
The interest group is one of the non-formal actors who also have the influence to play an active role in the dynamics of local politics with the various efforts and strategies they undertake. The presence of these organizations certainly creates a new dynamic at the social and political level. The mass base which is the source of the strength of mass organizations in moving, makes the mass organization a new commodity in the world of practical politics. This research focused on the Islamic Defenders Front (FPI) as one of the Islamic organizations. The discussion in this study seeks to reveal how much the role of the FPI towards the political dynamics that occurred during the 2017 DKI Jakarta Pilkada and the factors that caused FPI to play an active role in the dynamics. The research method used is a case study with a descriptive qualitative approach that can be in the form of words, pictures, quotations from interviews and official documents that support this research. Keywords: FPI, Interest Group, Al-Maidah 51, Action for Defending Islam